1997
DOI: 10.1016/s0896-6273(00)80953-8
|View full text |Cite
|
Sign up to set email alerts
|

A Role for 12-lipoxygenase in Nerve Cell Death Caused by Glutathione Depletion

Abstract: An early and highly specific decrease in glutathione (GSH) in the substantia nigra is associated with Parkinson's disease, and low levels of GSH lead to the degeneration of cultured dopaminergic neurons. Using immature cortical neurons and a clonal nerve cell line, it is shown that a decrease in GSH triggers the activation of neuronal 12-lipoxygenase (12-LOX), which leads to the production of peroxides, the influx of Ca2+, and ultimately to cell death. The supporting evidence includes: 1) inhibitors of arachid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
450
2
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 464 publications
(479 citation statements)
references
References 59 publications
23
450
2
4
Order By: Relevance
“…[24][25][26] Moreover, a few studies suggested the involvement of 5-or 12-LOX in pathways leading to neuronal death, such as kainic acid excitotoxicity, 27 apoptosis induced by prion peptide 28 and oxidative glutamate toxicity. 23 In this work, we show that blockade of 12-LOX expression protects cortical neurons from Ab-induced apoptosis, through disruption of a c-Jun-dependent apoptosis pathway. These findings suggest that 12-LOX might be considered as a new target for the treatment of AD.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…[24][25][26] Moreover, a few studies suggested the involvement of 5-or 12-LOX in pathways leading to neuronal death, such as kainic acid excitotoxicity, 27 apoptosis induced by prion peptide 28 and oxidative glutamate toxicity. 23 In this work, we show that blockade of 12-LOX expression protects cortical neurons from Ab-induced apoptosis, through disruption of a c-Jun-dependent apoptosis pathway. These findings suggest that 12-LOX might be considered as a new target for the treatment of AD.…”
Section: Introductionmentioning
confidence: 64%
“…A similar doublet pattern was already observed in previous studies on these cultures. 23 As shown in Figure 1a, pretreatment of cortical cells for 48 h with the antisense 12-LOX oligonucleotide induced an important decrease in the expression of 12-LOX protein. When normalized to corresponding actin levels, the effect of the oligonucleotide represented an 85% decrease in 12-LOX protein levels.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations